"Plans to Prosper You": Practical Theological Resourcing of Immigrant Churches for Civic Engagement - Christopher The (Indonesian Journal of Theology, 2015)
Immigrant churches function as interpretive interstices, where assimilation strategies are adjudicated and clashing cultural norms negotiated. Addressing purported Asian American malaise vis-à-vis civic engagement, I propose a practical theology method that privileges interlocution between a scriptural hermeneutics of diaspora and certain insights from social science. In the case of Asian American Christianity, how might immigrant churches more faithfully seek the "city's" shalom? What resources are available to evangelical migrants—and their children—for helping define identity and sense of belonging in this (new) land? How might immigrant churches better serve their ethnic constituencies within the context of American civic society? Thoughtful appropriation of the mantle of exile on the part of immigrant Christians helps to theologize that space of perpetual foreignness within contemporary American society. Immigrant churches are called to foster exilic interpretive imaginaries, in order to discern divine agency and faithful human response within the very contexts where God has dispersed God's people. One such example of doing practical theology is here offered.